2015
DOI: 10.1093/brain/awu393
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and amyloid pathologies are independent predictors of cognitive decline in normal elderly

Abstract: Vemuri et al. show that amyloid and vascular pathologies are independent processes, and that both are major drivers of cognitive decline in the elderly. Cognitive reserve as measured by educational/occupational level and mid/late-life cognitive activity seems to offset the deleterious effects of both pathologies on cognitive trajectories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
199
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 240 publications
(234 citation statements)
references
References 77 publications
32
199
2
1
Order By: Relevance
“…To argue that disproportionate vascular disease explains the current findings, vascular risk factors would need to have contributed to elevated brain amyloid, despite lack of evidence for this association. 25,26 If vascular and AD processes are simply additive, one would have predicted, in this study of individuals without dementia, less brain amyloid in blacks compared to whites (since more vascular disease is found in blacks, and, to have relatively normal cognition, high amounts of both amyloid and vascular disease would be unlikely). Thus, the vascular mechanism story does not fit the current observations.…”
mentioning
confidence: 80%
“…To argue that disproportionate vascular disease explains the current findings, vascular risk factors would need to have contributed to elevated brain amyloid, despite lack of evidence for this association. 25,26 If vascular and AD processes are simply additive, one would have predicted, in this study of individuals without dementia, less brain amyloid in blacks compared to whites (since more vascular disease is found in blacks, and, to have relatively normal cognition, high amounts of both amyloid and vascular disease would be unlikely). Thus, the vascular mechanism story does not fit the current observations.…”
mentioning
confidence: 80%
“…Here we assumed that there is minimal to no mechanistic interaction between AD and cerebrovascular measures early in the disease process 10, 11

Next, we chose an MRI modality and specific regions that satisfied all 3 criteria mentioned above (regional independence, variability, and sensitivity) as a cerebrovascular health biomarker in the discovery dataset.

In an independent validation dataset, we finally evaluated the utility of the cerebrovascular health biomarker in providing independent information about cognition in addition to amyloidosis.

…”
Section: Methodsmentioning
confidence: 99%
“…Here we assumed that there is minimal to no mechanistic interaction between AD and cerebrovascular measures early in the disease process 10, 11…”
Section: Methodsmentioning
confidence: 99%
“…The degree to which WMH contribute to progressive cognitive decline among older persons initially free of cognitive impairment also is poorly understood. Cross‐sectional studies have shown that WMH are associated with subtle cognitive decrements, particularly in perceptual speed and executive functions,10, 11, 12 but little data are available on the relation of WMH with cognitive decline among persons initially free of cognitive impairment 7, 13, 14, 15, 16. A better understanding of the degree to which WMH increase the risk of MCI and contribute to progressive decline in multiple cognitive systems is needed to facilitate strategies to promote cognitive health in old age.…”
Section: Introductionmentioning
confidence: 99%